2010
DOI: 10.1111/j.1471-4159.2010.06974.x
|View full text |Cite
|
Sign up to set email alerts
|

A single prenatal exposure to the endocrine disruptor 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin alters developmental myelination and remyelination potential in the rat brain

Abstract: J. Neurochem. (2010) 115, 897–909. Abstract Polychlorinated dibenzo‐dioxins, furans and dioxin‐like polychlorinated biphenyls are ubiquitous in foodstuffs of animal origin and accumulate in the fatty tissues of animals and humans. The most toxic congener is 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin (TCDD), a lipophilic endocrine‐disrupting molecule that accumulates in adipose tissue, placenta and milk. polychlorinated biphenyls and TCDD are known to interfere with thyroid hormone metabolism and signaling in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 74 publications
1
33
0
4
Order By: Relevance
“…Exposure to TCDD inhibited oligodendroglial lineage potential, resulting in a lower percentage of glial fibrillary acid protein-positive cells (Fernandez et al 2010). Furthermore, oligodendroglial maturation was inhibited as indicated by a decrease in CNPase-positive oligodendrocytes (Fernandez et al 2010).…”
Section: Developmental Programing Of Adipogenesis and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to TCDD inhibited oligodendroglial lineage potential, resulting in a lower percentage of glial fibrillary acid protein-positive cells (Fernandez et al 2010). Furthermore, oligodendroglial maturation was inhibited as indicated by a decrease in CNPase-positive oligodendrocytes (Fernandez et al 2010).…”
Section: Developmental Programing Of Adipogenesis and Obesitymentioning
confidence: 99%
“…Exposure to TCDD inhibited oligodendroglial lineage potential, resulting in a lower percentage of glial fibrillary acid protein-positive cells (Fernandez et al 2010). Furthermore, oligodendroglial maturation was inhibited as indicated by a decrease in CNPase-positive oligodendrocytes (Fernandez et al 2010). Exposure to the FR BDE-209 compromised adult NSC differentiation by inhibiting neurite outgrowth and neuron differentiation, but promoting glial cell differentiation (Zhang et al 2010).…”
Section: Developmental Programing Of Adipogenesis and Obesitymentioning
confidence: 99%
“…[2][3][4][5][6] Dioxin and related compounds are the cause of neurological disorders in humans and experimental animals as well as their offspring in the perinatal period after exposure to these compounds through the placenta and milk in prenatal and postnatal periods. [7][8][9] Dioxins significantly affect brain development in the prenatal and postnatal periods associated with the time of breastfeeding by mothers intoxicated with dioxins. [10][11][12][13] Changes caused by dioxins in the central nervous system (CNS) in pre-and postnatal periods lead to later changes in life.…”
Section: Introductionmentioning
confidence: 99%
“…Functional disorders of the brain structures, including the cerebellum and diencephalon, should also be associated with changes in thyroid hormone levels and estrogen receptors (ER) induced by dioxins. 9,[14][15][16][17] It was shown that dioxins lead to the underdevelopment of the bones and teeth in both humans and animals as a result of mineralization disorders. [18][19][20] It was found that after birth there is a significant concentration of dioxins in the breast milk, correlating negatively with a newborn head circumference.…”
Section: Introductionmentioning
confidence: 99%
“…As primeiras células precursoras de oligodendrócitos, responsáveis pela produção da mielina no SNC, aparecem por volta da nona semana em humanos e são caracterizadas pela expressão de Olig 1, receptor alfa do fator de crescimento derivados de plaquetas (PDGFαR) e de NG2. A maturação dos oligodendrócitos é marcada pela expressão da proteína básica de mielina (PBM) e da proteína proteolipídeo (PLP) (FERNÁNDEZ et al, 2010). Em roedores, no primeiro dia de vida pós-natal os oligodendrócitos maduros já expressam marcadores como a PBM na medula espinhal (DORETTO et al, 2011).…”
Section: Mielinizaçãounclassified